2021
DOI: 10.1016/j.bioactmat.2021.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Collagen/hyaluronan based hydrogels releasing sulfated hyaluronan improve dermal wound healing in diabetic mice via reducing inflammatory macrophage activity

Abstract: Sustained inflammation associated with dysregulated macrophage activation prevents tissue formation and healing of chronic wounds. Control of inflammation and immune cell functions thus represents a promising approach in the development of advanced therapeutic strategies. Here we describe immunomodulatory hyaluronan/collagen (HA-AC/coll)-based hydrogels containing high-sulfated hyaluronan (sHA) as immunoregulatory component for the modulation of inflammatory macrophage activities in disturbed wound healing. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 94 publications
1
47
0
Order By: Relevance
“…There are different types of COL (type I, II, III, IV and V, among others) present depending on their function in the body [ 165 ]. Thus, due to its abundance in nature, availability (porcine, bovine and marine), biodegradability and biocompatibility and excellent cell viability values (>80%), COL is an optimal candidate for hydrogel manufacture for wound healing [ 66 , 71 ], TE [ 67 , 72 ], drug delivery [ 68 ] and ophthalmic applications [ 73 ]. Nevertheless, even though ex vivo assays with COL-based hydrogels have been carried out with human skin models [ 71 ], more in vivo experiments are necessary to characterize COL-based hydrogels for other applications, for example, bone tissue engineering [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are different types of COL (type I, II, III, IV and V, among others) present depending on their function in the body [ 165 ]. Thus, due to its abundance in nature, availability (porcine, bovine and marine), biodegradability and biocompatibility and excellent cell viability values (>80%), COL is an optimal candidate for hydrogel manufacture for wound healing [ 66 , 71 ], TE [ 67 , 72 ], drug delivery [ 68 ] and ophthalmic applications [ 73 ]. Nevertheless, even though ex vivo assays with COL-based hydrogels have been carried out with human skin models [ 71 ], more in vivo experiments are necessary to characterize COL-based hydrogels for other applications, for example, bone tissue engineering [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…161 The sHA-releasing hydrogels downregulated the inflammatory activities of bone marrow-derived and tissue-resident macrophages in vitro, improved the vascularization, and accelerated the formation of new tissues for wound healing. 161 In the second approach, it is possible to alleviate and inhibit inflammation by loading antiinflammatory drugs for slow release from the hydrogel. 162,163 Chatterjee et al developed a pH and temperature dual-responsive hydrogel drug delivery system for loading of gallic acid, which is a main ingredient of traditional Chinese medicine cortex moutan.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…This M1 to M2 differentiation is associated with IL-4 and IL-10, in line with HMW-HA stimulating production of immunosuppressive M2 macrophages [51]. In fact, one recent study showed that a sulfated HA/collagen hydrogel improved diabetic wound healing in mice by hindering the TLR pathway and promoting M2 polarization of macrophages [40], supporting the crosstalk of HA between inflammatory cells and the wound ECM. Conversely, LMW-HA, acting through TLRs 2/4, induces M1 macrophage differentiation during the inflammatory stage of wound healing [39].…”
Section: Macrophagesmentioning
confidence: 81%